2017
DOI: 10.1016/j.lisr.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' beliefs about library visits: A theory-based study of formative research

Abstract: A three-phase program of formative research was used to examine decisions to visit libraries with young children. • Caregivers predominately resided in a low socioeconomic area. • Social cognitive factors influenced caregivers' decisions to visit the library. • A range of beliefs were identified that could be targets for future intervention to promote library visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…While the world of school standards can be intimidating, and public libraries have traditionally separated themselves from schools and education (Albright et al, 2009), it is imperative that public libraries begin to embrace the roles that they can and do play in school readiness beyond contributions to literacy development. This is particularly important given the findings of a recent study conducted in Canada pointing to school readiness as the primary motivator for caregivers who bring their children to storytime (Peterson, 2012), and a study in Australia identifying learning and reading encouragement as the primary motivators of parents and caregivers to bring young children to the library (Schmidt and Hamilton, 2017). Perhaps, however, rather than a disregard for school readiness, the directors’ low rating of the concept in the present study may simply point to a lack of awareness or understanding of the term.…”
Section: Discussionmentioning
confidence: 99%
“…While the world of school standards can be intimidating, and public libraries have traditionally separated themselves from schools and education (Albright et al, 2009), it is imperative that public libraries begin to embrace the roles that they can and do play in school readiness beyond contributions to literacy development. This is particularly important given the findings of a recent study conducted in Canada pointing to school readiness as the primary motivator for caregivers who bring their children to storytime (Peterson, 2012), and a study in Australia identifying learning and reading encouragement as the primary motivators of parents and caregivers to bring young children to the library (Schmidt and Hamilton, 2017). Perhaps, however, rather than a disregard for school readiness, the directors’ low rating of the concept in the present study may simply point to a lack of awareness or understanding of the term.…”
Section: Discussionmentioning
confidence: 99%
“…These programs provide an interactive and engaging environment that enhances language development, vocabulary acquisition and pre-reading skills (Ouda, 2022). In addition to story times, public libraries organize early literacy workshops that offer parents and caregivers guidance on how to support their children’s literacy development (Schmidt and Hamilton, 2017). These workshops provide valuable information on the importance of early literacy, strategies for reading aloud, and the selection of appropriate books.…”
Section: Public Libraries Are For Everyone In the Communitymentioning
confidence: 99%
“…Accordingly, emerging research has investigated caregivers' beliefs or perceptions of library services and programmes for children. For example, Schmidt and Hamilton (2017) identified "educational and reading benefits for their child" as a primary motivation for caregivers to visit the library with their child (p. 270) and identified a "lack of time" and "boisterous[ness of children]" as factors that discourage caregivers to visit the library (p. 272). Clark (2017) found that caregivers strongly agree that emergent literacy programmes in public libraries foster child learning with a particular focus on social interaction in which public librarians are responsive and nurturing, and the environments are warm, caring, and supportive for children.…”
Section: Related Literaturementioning
confidence: 99%
“…In addition to participating in activities, librarians in the three countries reported that caregivers with preschool children aged five and six tended to engage in conversations with them about book selection and parent-child shared reading. Indeed, Schmidt and Hamilton (2017) also found that promoting children's learning and encouraging reading serve as main reasons underpinning caregivers' beliefs about library visits.…”
Section: Support Servicesmentioning
confidence: 99%
See 1 more Smart Citation